Meningkatkan Hasil Belajar PJOK Materi Senam Lantai dengan Menggunakan Metode Demonstrasi di Kelas IV SD Negeri 28 Payakumbuh Semester Genap T.P 2021/2022 - Munardi Munardi (Departement of Mathematics Education, 2022)
This study aims to see and analyze the increase in PJOK learning outcomes for students in gymnastics material through the demonstration method in grade V even semester SDN 28 Payakumbuh TP 2021/2022. This research was conducted using the Classroom Action Research method which consisted of three cycles, where each cycle consisted of; planning, action, observation and reflection. It was carried out from January to June 2022. Data was processed in each cycle and then analyzed using percentages. The results obtained from this study are that using the demonstration method can improve student PJOK learning outcomes. This is evident from the increase in student learning activities in each cycle. The conclusion obtained from this study is that the use of demonstration methods can improve student learning outcomes.